2017
DOI: 10.3389/fnhum.2017.00248
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Video Gaming: A Systematic Review

Abstract: Background: Video gaming is an increasingly popular activity in contemporary society, especially among young people, and video games are increasing in popularity not only as a research tool but also as a field of study. Many studies have focused on the neural and behavioral effects of video games, providing a great deal of video game derived brain correlates in recent decades. There is a great amount of information, obtained through a myriad of methods, providing neural correlates of video games.Objectives: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
162
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 174 publications
7
162
1
15
Order By: Relevance
“…Our study was not designed to address any of these factors; however, prompted by our participant demographics, which indicated that male participants were substantially more likely to regularly play computer games than female participants, we assessed if there was a relation between participants' report of regular computer gaming and virtual DMP and mental rotation performance. Previous studies have linked computer gaming to better performance on a number of cognitive tests, including the mental rotation test (Boot, Kramer, Simons, Fabiani, & Gratton, ; Palaus, Marron, Viejo‐Sobera, & Redolar‐Ripoll, ; Terlecki & Newcombe, ), to an increase in hippocampal grey matter, and a shift from egocentric to allocentric navigation strategies (Kühn, Gleich, Lorenz, Lindenberger, & Gallinat, ). Consistent with these findings, our additional analyses suggest a positive relationship between gaming experience and some aspects of mental rotation and virtual DMP performance, which may reflect that gaming improves performance or that the cognitive abilities that improve mental rotation and virtual DMP performance make it more likely to engage in regular computer gaming (Boot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was not designed to address any of these factors; however, prompted by our participant demographics, which indicated that male participants were substantially more likely to regularly play computer games than female participants, we assessed if there was a relation between participants' report of regular computer gaming and virtual DMP and mental rotation performance. Previous studies have linked computer gaming to better performance on a number of cognitive tests, including the mental rotation test (Boot, Kramer, Simons, Fabiani, & Gratton, ; Palaus, Marron, Viejo‐Sobera, & Redolar‐Ripoll, ; Terlecki & Newcombe, ), to an increase in hippocampal grey matter, and a shift from egocentric to allocentric navigation strategies (Kühn, Gleich, Lorenz, Lindenberger, & Gallinat, ). Consistent with these findings, our additional analyses suggest a positive relationship between gaming experience and some aspects of mental rotation and virtual DMP performance, which may reflect that gaming improves performance or that the cognitive abilities that improve mental rotation and virtual DMP performance make it more likely to engage in regular computer gaming (Boot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also many previous studies reporting DLPFC deactivations during virtual reality visuo‐motor tasks and active video game playing . The deactivation of DLPFC appeared to be modulated by the genre of the game, but not the age or the performance level of the player . Flow experience during video game playing, but not passive viewing of video game contents , was associated with DLPFC deactivations .…”
Section: Discussionmentioning
confidence: 81%
“…The reasons why DLPFC could become deactivated during virtual reality visuo‐motor tasks/video game playing are still poorly understood, and remain a subject of debate . It has been proposed that lateral PFC could be activated in common during rest, and the recruitment of lateral PFC during rest supports higher cognitive functions that would occur in specific tasks, such as visual imaginary and memory retrieval .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the novel assessment tools should provide investigators in the psychological and biomedical sciences with research-grade cognitive and psychological metrics. Technological advances along with a strongly grown computer literacy in the general population and widespread familiarity with computer games (Granello and Wheaton 2004;Palaus et al 2017) open up a plethora of possibilities for the operationalization of psychological research questions. Leveraging gamification to repeatedly obtain behavioral samples paves the way for a next-generation highthroughput psychometric toolset.…”
Section: Discussionmentioning
confidence: 99%